Dinamika Gaya Hidup Konsumtif dalam Fenomena Pinjol pada Masyarakat Kota - Retno Kusumawati; Sujarwo Sujarwo; Desy Safitri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The phenomenon of online loans has emerged as a financial innovation that transforms the pattern of access to funds within urban communities. The convenience of obtaining loans without complex requirements has contributed to the rise of a consumerist lifestyle, especially among the younger generation. This study aims to analyze the correlation between the use of online loans and the dynamics of consumerist lifestyles in urban society. By employing a literature review and descriptive-qualitative analysis methods, the research reveals that low financial literacy, social pressure, and the influence of social media intensify the tendency toward instant loan-based consumerist behavior. Psychological factors such as FOMO (Fear of Missing Out) and the philosophy of YOLO (You Only Live Once) further reinforce this consumerist behavioral pattern. The results of the study show that the phenomenon of online loans not only impacts financial issues but also causes psychological stress and shapes compulsive consumption patterns.